Model-based planning of test cases and test scenarios to support engineering of Cyber-Physical Systems - Gräßler, Iris; Ebel, Marcel; Pottebaum, Jens (2024 IEEE International Symposium on Systems Engineering (ISSE))
Engineering methodologies for Cyber-Physical Systems (CPS) call for planning simulations and physical testing in early phases of product creation. Even in Model-Based Systems Engineering, there is a lack of systematic support that results in avoidable costs and iterations in the engineering process. Planning test cases and test scenarios along the product engineering process is not sufficiently integrated in terms of support especially for verification and validation engineers. Based on a systematic literature review, concepts for model-based planning of testing are developed. Characteristics of test cases and test scenarios of CPS are systematically identified. Generic templates for the creation of test cases and scenarios are derived. Based on the templates, a System Modeling Language (SysML) profile extension is developed which enables intuitive modelling of test cases and scenarios. The SysML profile is evaluated in a sample System-of-Systems in Disaster Response. It subsumes various types of sensor systems like rescue robotics, data science algorithms and visualization technologies like Augmented Reality to support decisions in extreme weather events. The templates and SysML profile significantly add value for engineers in the early and systematic planning of verification and validation.
Keywords: Systems Engineering; Systems verification; System testing

Leibniz, Gottfried Wilhelm, General Inquiries on the Analysis of Notions and Truths, edited with an English translation by Massimo Mugnai, Oxford University Press: Oxford 2021 (BSHP New Texts in the History of Philosophy) - Peckhaus, Volker (Mathematical Reviews, MR457231)

Fraenkel, Adolf Abraham Halevi - Peckhaus, Volker (NDB-online, veröffentlicht am 01.07.2024)

Knowledge Transfer for Microgrids Sustainability – the Case of East Africa - Bogere, Paul

Operative Beziehungen erkennen, beschreiben und nutzen – Initiierung von Lernprozessen unter Einbeziehung der App ‚Rechenfeld‘ - Dettelbach, Andrea; Häsel-Weide, Uta (Förderung prozessbezogener Kompetenzen mit digitalen Medien. Mit mathematischen Objekten und Werkzeugen arbeiten)

Zur Dauerfrage nach der Positionalität von Religionslehrkräften - Woppowa, Jan; Hüster, Jonas Maximilian (engagement. Zeitschrift für Erziehung und Schule)

Im Gespräch. Studienhandbuch zum jüdisch-christlichen Dialog

Contextualization for Generating FAIR Data: A Dynamic Model for Documenting Research Activities - Altun, Osman; Hinterthaner, Marc; Barienti, Khemais; Nürnberger, Florian; Lachmayer, Roland; Mozgova, Iryna; Koepler, Oliver; Auer, Sören (IFIP Advances in Information and Communication Technology)

DFT‐Assisted Investigation of the Electric Field and Charge Density Distribution of Pristine and Defective 2D WSe2 by Differential Phase Contrast Imaging - Groll, Maja; Bürger, Julius; Caltzidis, Ioannis; Jöns, Klaus D.; Schmidt, Wolf Gero; Gerstmann, Uwe; Lindner, Jörg K. N. (Small)
Abstract Most properties of solid materials are defined by their internal electric field and charge density distributions which so far are difficult to measure with high spatial resolution. Especially for 2D materials, the atomic electric fields influence the optoelectronic properties. In this study, the atomic‐scale electric field and charge density distribution of WSe 2 bi‐ and trilayers are revealed using an emerging microscopy technique, differential phase contrast (DPC) imaging in scanning transmission electron microscopy (STEM). For pristine material, a higher positive charge density located at the selenium atomic columns compared to the tungsten atomic columns is obtained and tentatively explained by a coherent scattering effect. Furthermore, the change in the electric field distribution induced by a missing selenium atomic column is investigated. A characteristic electric field distribution in the vicinity of the defect with locally reduced magnitudes compared to the pristine lattice is observed. This effect is accompanied by a considerable inward relaxation of the surrounding lattice, which according to first principles DFT calculation is fully compatible with a missing column of Se atoms. This shows that DPC imaging, as an electric field sensitive technique, provides additional and remarkable information to the otherwise only structural analysis obtained with conventional STEM imaging.

Die steel design for additive manufacturing - Hengsbach, Florian; Bürger, Julius; Andreiev, Anatolii; Biggs, Krista; Fischer-Bühner, Jörg; Lindner, Jörg K.N; Hoyer, Kay-Peter; Olson, Gregory B.; Schaper, Mirko (Acta Materialia)

Auch Ärzte erzählen Geschichten: Medizinisches Wissen und Narration in Blogs und Podcasts - Mildorf, Jarmila (Re:visit: Humanities and Medicine in Dialogue)

ADMM-TGV image restoration for scientific applications with unbiased parameter choice - Zietlow, Christian; Lindner, Jörg K. N. (Numerical Algorithms)
Abstract Image restoration via alternating direction method of multipliers (ADMM) has gained large interest within the last decade. Solving standard problems of Gaussian and Poisson noise, the set of “Total Variation” (TV)-based regularizers proved to be efficient and versatile. In the last few years, the “Total Generalized Variation” (TGV) approach combined TV regularizers of different orders adaptively to better suit local regions in the image. This improved the technique significantly. The approach solved the staircase problem inherent of the first-order TV while keeping the beneficial edge preservation. The iterative minimization for the augmented Lagrangian of TGV problems requires four important parameters: two penalty parameters $${ρ }$$ ρ and $${η }$$ η and two regularization parameters $${λ _{0}}$$ λ 0 and $${λ _{1}}$$ λ 1 . The choice of penalty parameters decides on the convergence speed, and the regularization parameters decide on the impact of the respective regularizer and are determined by the noise level in the image. For scientific applications of such algorithms, an automated and thus objective method to determine these parameters is essential to receive unbiased results independent of the user. Obviously, both sets of parameters are to be well chosen to achieve optimal results, too. In this paper, a method is proposed to adaptively choose optimal $${ρ }$$ ρ and $${η }$$ η values for the iteration to converge faster, based on the primal and dual residuals arising from the optimality conditions of the augmented Lagrangian. Further, we show how to choose $${λ _{0}}$$ λ 0 and $${λ _{1}}$$ λ 1 based on the inherent noise in the image.
Keywords: Applied Mathematics

Auswirkungen der Einführung eines Verlustrücktrags in Österreich. Ergebnisse einer Simulationsstudie - Sureth-Sloane, Caren; Giese, Henning (SWK Steuer- und WirtschaftsKartei)

Micro Archives. Künstlerische Arbeiten 2019-2024. - Autsch, Sabiene

Chips - Autsch, Sabiene (Lexikon der Lebensmittel als Kunstmaterial. [ Von Apfel bis Zucker])

Peter von Lindpaintner, Johann Wolfgang von Goethe, Carl Seydelmann, Ouverture, Entreacte, Chöre und Lieder zu Goethes Faust nach der szenischen Einrichtung von Carl Seydelmann (1832) - Bachmann, Tobias; Tumat, Antje; Frömmel, Lena; Münzmay, Andreas

„Türck und Heide sind verschanzt hinter den Bergen, die Warte ist die feste Burg, daran sie zerschellen.“ Inszenierungen von kulturellem Fanatismus in Feridun Zaimoglus Evangelio - Schulte Eickholt, Swen (Der Neuer Weltengarten 2023. Jahrbuch für Literatur und Interkulturalität)
Keywords: Zaimoglu; historischer Roman; deutsche Gegenwartsliteratur; Kontrafaktik; Luther; Evangelio

Synergies of Deep and Classical Exploratory Landscape Features for Automated Algorithm Selection - Seiler, Moritz; Skvorc, Urban; Doerr, Carola; Trautmann, Heike (Learning and Intelligent Optimization - 18th International Conference, LION 18, Ischia Island, Italy, June 9-13, 2024, Revised Selected Papers)

Parallel Problem Solving from Nature - PPSN XVIII - 18th International Conference, PPSN 2024, Hagenberg, Austria, September 14-18, 2024, Proceedings, Part III

Parallel Problem Solving from Nature - PPSN XVIII - 18th International Conference, PPSN 2024, Hagenberg, Austria, September 14-18, 2024, Proceedings, Part I